Analysis of The Character of Bi Nu "Mengjiangnu” by Contrasting Women’s View on Husband Through Ages - Wiliam Wijaya (Humaniora, 2013)
Novel BINU is one of Sutong’s excellent works. Through Binu, the character which is called Meng jiangnu, could see weak women in order to find her lovely husband exhausted all its effort to walk a long road. Meng jiangnu’s story is one of the four chinese’s ancient legendary loves. Other are  Niu Lang Zhinu, Liang Sanbo Yu Zhu Ying Tai, and Bai She Zhuan, have been widely spread for thousands of years. The legend of Meng jiangnu has been spread with oral tradition in folkloric. The earliest legend can be traced back to the "Zuo Zhuan".  Through Novel BINU, the author wants to observe “Examining Meng jiangnu characterization by contrasting ways of women’s view through ages in Novel BINU by Sutong”. And then, the author also introduces Novel BINU, Meng jiangnu myths, and through XINGGE, to examine the characterization of Meng jiangnu. By examining the character Meng jiangnu, the author finds that Meng jiangnu had melancholy and choleric character. Both characters are shown out in difficulties. Meng jiangnu treated her husband better than women in that age. The women in that age just cried in waiting the fate changes.